PERAN KOMUNIKASI ANTAR BUDAYA TERHADAP HUBUNGAN YANG HARMONIS DI JEMAAT GMII SYALOM MEDAN - Elisabeth Sitepu; Rumenta Astuti Simangunsong (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
This study aims at determining the role of intercultural communication carried out by the congregation of the GMII Syalom Church Medan having different cultural backgrounds and finding out the supporting and inhibiting factors in conducting intercultural communication carried out by the congregation of GMII Syalom Medan Church. Research method used is a qualitative descriptive approach with data collection techniques through interviews, document studies, observations and literature. The design of this research is expected to provide abstract and general answers to questions arising in a basic research. Research f of this indings show that (1) The patterns of intercultural communication carried out by the congregations of the Church of GMII Syalom Medan with different cultural backgrounds are in the form of symbolic intercultural communication patterns and direct intercultural communication patterns (2) Supporting factors contained in this intercultural communication process are the ability to communicate, attitudes to accept each other differences, friendly attitude and courtesy, the ability to adapt, a sense of family in the congregation, interest when communicating, and understanding of the Word of God. Whereas the inhibiting factors of intercultural communication are individual character, perception of communication actors, influence of other cultures, and language differences.